Lack of evolutionary changes identified in SARS-CoV-2 for the re-emerging outbreak of COVID-19 in Beijing, China - Yang Li; Yunjun Zhang; Mifang Liang; Yi Zhang; Xuejun Ma; Yong Zhang; Xiaohua Zhou (Elsevier, 2022)
Although significant achievements have shown that the coronavirus disease 2019 (COVID-19) resurgence in Beijing, China, was initiated by contaminated frozen products and transported via cold chain transportation, international travelers with asymptomatic symptoms or false-negative nucleic acid may have another possible transmission mode that spread the virus to Beijing. One of the key differences between these two assumptions was whether the virus actively replicated since, so far, no reports showed viruses could stop evolution in alive hosts. We studied severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sequences in this outbreak by a modified leaf-dating method with the Bayes factor. The numbers of single nucleotide variants (SNVs) found in SARS-CoV-2 sequences were significantly lower than those called from B.1.1 records collected at the matching time worldwide (P = 0.047). In addition, results of the leaf-dating method showed ages of viruses sampled from this outbreak were earlier than their recorded dates of collection (Bayes factors > 10), while control sequences (selected randomly with ten replicates) showed no differences in their collection dates (Bayes factors < 10). Our results which indicated that the re-emergence of SARS-CoV-2 in Beijing in June 2020 was caused by a virus that exhibited a lack of evolutionary changes compared to viruses collected at the corresponding time, provided evolutionary evidence to the contaminated imported frozen food should be responsible for the reappearance of COVID-19 cases in Beijing. The method developed here might also be helpful to provide the very first clues for potential sources of COVID-19 cases in the future.